Microbiota characterization of atmospheric cold plasma treated blueberries. (15th April 2023) - Sun, Hao; Duan, Yaoke; Li, Huandong; Hu, Xiaoxia; Li, Bing; Zhuang, Jie; Feng, Junxia; Ma, Ruonan; Jiao, Zhen
Abstract: Atmospheric cold plasma (ACP) holds great potential in postharvest preservation of blueberries, yet ACP-induced microbiota alterations in blueberries have rarely been researched. Herein, the effects of ACP on the microbiota community composition and diversity as well as their correlation with anthocyanin accumulation in blueberries during storage were investigated. The results showed that ACP-induced microbiota inactivation was not selective at the phylum level, but the proportion of Bacteroides and Faecalibacterium at the genus level was increased. MND1, Curtobacterium, Blastococcus and Owenweeksia can function as biomarkers of ACP-mediated sterilization. The surviving microbiota were less pathogenic and more sensitive to environmental stresses. The anthocyanin concentration of blueberries was slightly affected by the 10-min ACP treatment but decreased after the 20-min ACP treatment. Correlation analysis demonstrated that Alternaria was positively correlated with all anthocyanins, while Bacteroides, Ruminnococcus-torques-group, Lachnoclostridium and Escherichia-Shigella were negatively correlated with over four anthocyanins. This study will help evaluate the performance and risk of ACP-mediated postharvest preservation of blueberries . Highlights: Atmospheric cold plasma (ACP) could restrain microbiota in blueberries. ACP-induced microbiota inactivation was selective at genus level. The surviving microbiota were less pathogenic. MND1, Curtobacterium, Blastococcus and Owenweeksia can be the biomarkers. Alternaria was positively correlated with anthocyanins of ACP treated blueberries.